Tourism promotion in developing countries - Waldemar B. Hasselblatt (Intereconomics, 1973)
When announcing its ideas on development policy in the Second Development Decade which began in 1971, the Federal Government said that it “wishes to promote tourism in sultable less developed countries (LDCs) through improvement of the infrastructure, especially transport, provision of accommodation and training of the required personnel, making use of development banks in suitable cases”.
Keywords: 330; Development Policy